Intravital Imaging Techniques for Biomedical and Clinical Research. Issue 5 (30th December 2019) - Coste, Anouchka; Oktay, Maja H.; Condeelis, John S.; Entenberg, David
Abstract: Intravital imaging, the direct visualization of cells and tissues within a living animal, is a technique that has been employed for the better part of a century. The advent of confocal and multiphoton microscopy has dramatically improved the power of intravital imaging, making it possible to obtain optical sections of tissues non‐destructively. This review discusses the various techniques used for intravital imaging, describes how intravital imaging provides information about cellular and tissue dynamics not possible to be garnered by other techniques, and details several ways in which intravital imaging is making a direct impact on the clinical care of patients. © 2019 International Society for Advancement of Cytometry